تأثير التقوية على متانة انبعاج الألواح في إنشاءات السفن - غالب أحمد (Tishreen University, 2019)
تقسّم الألواح في إنشاءات السفن إلى ألواح مستطيلة صغيرة باستخدام عناصر تقوية طولية أو عرضية. لهذه الألواح بعض القيود على أطرافها تقدّم من خلال صلابة الفتل لعناصر التقوية. يهدف هذا البحث إلى توضيح المعالم الرئيسية لانبعاج الألواح المقواة، وتقديم الطريقة العامة لحل معظم الحالات التي يمكن أن تستخدم أحمالاً متنوعة. استخدمت الطريقة التحليلية، لحل المعادلات التفاضلية التي تدير الانبعاج بالاستعانة بطاقة الانفعال. للحصول على فكرة عن مقدار إجهاد الانبعاج طبقا للصيغ المعتبرة في البحث، تمّ دراسة تأثير كلّ من التقوية الطولية والعرضية على متانة انبعاج اللوح. بينت النتائج بأن قيمة متانة الانبعاج للوح باستخدام التقوية الطولية أكبر بحوالي أربع مرات بالمقارنة مع التقوية العرضية. وهذا يقدّم مزايا كبيرة للتقوية الطولية على التقوية العرضية في إنشاءات السفن. The Plating of the structure of a ship is divided into small rectangular plates, using Longitudinal and Transverse Stiffeners. These panels have some constraints at the edges, by the torsional  rigidity of the Stiffeners. The purpose of this research is to explain the principal features of stiffened panel buckling, to present  the analytical method of solution  for solving the governing differential equations . To obtain some idea of the magnitude of the buckling stress according to the considered formulae  here, an  influence of longitudinal and transverse stiffeners on the buckling strength of plating is studied. The results show that the buckling  strength of plating with longitudinal stiffening is nearly four times as a great as when transverse stiffening is employed.  This presents the great advantages of longitudinal stiffening over transverse stiffening in ship structures